Studies Of Amino Acid Component And Microflora In Climbing Perch Wadi - Khairina, Rita; Khotimah, Iin Khusnul (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The research of microflora and amino acids component in climbing perch wadi had been done.Â Aims of this research are to know amino acids composition in fresh fish and climbing perch wadi; and to know kind of halofilic bacterial (until genus level) that have a role during climbing perch wadi fermentation process.Â Wadi is tradisional fermentationÂ product of fish that have fishÂ fermentation specific aroma with salty taste.Â Was the processes by dry pickling in closed chamber with hight concentration salt (â¥ 25% w/w). The result, arranged component of amino acids in fresh climbing perch is the sameÂ of climbing perch wadi, but the compositions are decreased during fermentation process. Isolation, characterization and identification of bacterial were done, obtain three kinds ofÂ bacterial fromÂ Acinetobacter, Enterobacteriaceae, and Brucella genus, and the dominant genus group is Acinetobacter. Â Key words: microflora, amino acid component, wadi, climbing perch